THE ROLE OF SOCIAL SUPPORT IN CHARACTER TRANSFORMATION: A STUDY OF GAIL HONEYMAN’S ELEANOR OLIPHANT IS COMPLETELY FINE - Ntoy, Kania Adeline; Maru, Mister Gidion; Husain, Sabrina W. J. (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
Social support is a crucial pillar in psychological recovery and an individual's ability to establish social interactions. Eleanor Oliphant Is Completely Fine illustrates how forms of social support can catalyze changes in the main character's behavior and mental health. However, previous research on Taylor's classifications of social support in novels remains very limited. The objective of this research was to identify and analyze the reflection of the three types of social support in the novel Eleanor Oliphant Is Completely Fine by Gail Honeyman and describe the role of each in plot and character development. The approach in this study is Genetic Structuralism integrated with Social Support Theory. Data were collected in the form of dialog quotations, narratives, and descriptions that reflected social support, then classified according to Taylor's theory. The findings of the study showed that emotional support was most prominent, followed by informational support and instrumental support. Emotional support provides Eleanor with the empathy and understanding needed to rebuild her sense of self, while informational and informational and instrumental supports offer practical guidance and tangible assistance that empower her recovery. Together, these social supports drive Eleanor's healing and willingness to engage socially. The structuralist genetic approach reveals the author's personal perspectives on loneliness and kindness that emerge as foundational themes, illustrating how interpersonal connections are essential for personal transformation and social reintegration. This study highlights how literature reflects psychological realities and suggests that portraying social support can deepen understanding in both literary and psychological fields, encouraging writers to emphasize everyday kindness in character recovery.